Hubungan Paritas Dan Usia Ibu Dengan Kejadian Sectio Caesarea Di RSUD Ulin Banjarmasin Tahun 2023 - Norbaiti Norbaiti; Rr. Sri Nuriaty; Didi Ariady; Noor Anisa (NAJ Nursing Applied Journal, 2024)
Sectio Caesarea (SC) is a delivery method in which the baby is born through an incision in the abdominal wall and the opened or incised uterus, while keeping the uterus intact. In recent years, normal childbirth has been considered risky and challenging, leading to the emergence of cesarean section as an alternative option for some women undergoing labor and delivery. High-risk childbirth can have adverse effects on both the baby and the mother. The repeated pregnancies can weaken the uterus, causing complications in both pregnancy and delivery. Therefore, appropriate measures are necessary to save both the baby and the mother. The aim of this research is to determine the relationship between parity and maternal age with the incidence of cesarean section at Ulin Regional General Hospital in Banjarmasin. The research method used is a descriptive correlational approach, conducted in October 2023. The population in this study includes all patients who delivered through the CS method at Ulin Regional General Hospital in Banjarmasin, with the sample taken from the entire population that meets the criteria or saturation sample criteria. The data used are secondary data that already exist. Based on the results of the Chi-Square statistical analysis, the p-value is 0.000 < α (0.05), thus it can be concluded that H0 is rejected, and Ha is accepted, indicating a relationship between parity and maternal age with the incidence of cesarean section at Ulin Regional General Hospital in Banjarmasin.